Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1175/jcli-d-16-0652.1
|View full text |Cite
|
Sign up to set email alerts
|

How Suitable is Quantile Mapping For Postprocessing GCM Precipitation Forecasts?

Abstract: GCMs are used by many national weather services to produce seasonal outlooks of atmospheric and oceanic conditions and fluxes. Postprocessing is often a necessary step before GCM forecasts can be applied in practice. Quantile mapping (QM) is rapidly becoming the method of choice by operational agencies to postprocess raw GCM outputs. The authors investigate whether QM is appropriate for this task. Ensemble forecast postprocessing methods should aim to 1) correct bias, 2) ensure forecasts are reliable in ensemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
104
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 153 publications
(119 citation statements)
references
References 56 publications
8
104
1
6
Order By: Relevance
“…Since RPP-S is built 5 upon the Bayesian joint probability (BJP) modelling approach, it explicitly models the correlation between the forecasts and observations, and thus takes into account model skill in the calibration. Our results add to the findings of Zhao et al (2017) who studied the post-processing of monthly rainfall forecasts from POAMA (Australia's GCM preceding ACCESS-S). While Zhao et al (2017) demonstrated that QM is very effective for bias correction, they did not consider accumulated totals.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Since RPP-S is built 5 upon the Bayesian joint probability (BJP) modelling approach, it explicitly models the correlation between the forecasts and observations, and thus takes into account model skill in the calibration. Our results add to the findings of Zhao et al (2017) who studied the post-processing of monthly rainfall forecasts from POAMA (Australia's GCM preceding ACCESS-S). While Zhao et al (2017) demonstrated that QM is very effective for bias correction, they did not consider accumulated totals.…”
Section: Discussionsupporting
confidence: 75%
“…Our results add to the findings of Zhao et al (2017) who studied the post-processing of monthly rainfall forecasts from POAMA (Australia's GCM preceding ACCESS-S). While Zhao et al (2017) demonstrated that QM is very effective for bias correction, they did not consider accumulated totals. In our study, we find that the RPP-S forecasts are less biased and more reliable than QM forecasts for accumulated totals.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…There have been some criticisms raised lately regarding the 10 applicability of quantile mapping for bias adjusting seasonal data (e.g. Zhao et al, 2017). They point out that although quantile mapping approaches are effective at bias correction they cannot ensure reliability in forecast ensemble spread or guarantee coherence.…”
Section: Dynamical Modelling Ensemble (De)mentioning
confidence: 99%